1999
DOI: 10.2151/jmsj1965.77.6_1177
|View full text |Cite
|
Sign up to set email alerts
|

Quasi 4 Day Mode Observed by a Boundary Layer Radar at Serpong (6°S, 107°E), Indonesia

Abstract: A spectral analysis of lower tropospheric winds, observed by the Boundary Layer Radar (BLR) at Serpong (60S, 1070E) in West Java, Indonesia during 1992/93, 1993/94, and 1994/95 rainy seasons reveals a pronounced spectral peak, at a period near 4 days. Filtered analysis of this quasi 4 day mode (Q4DM) shows almost an in-phase structure in the vertical. The CANAL (Global Objective Analysis by Japan Meteorological Agency) data for 1992/93 rainy seasons shows that in general the meridional wind component, at the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…For example, Takayabu et al (1996) found out a quasi-2 day mode from cloud activities by GMS, rainfall data by meteorological radars, rawinsondes, a UHF wind profiler and meteorological buoy data over the equatorial Pacific, and identified it with westward propagating inertio-gravity waves. Widiyatmi et al (1999) found out a quasi-4 day mode in the Serpong BLR data, and GMS data in rainy seasons of Java Island, and considered that it may be mixed Rossby-gravity waves propagating westward. However, these are shorter than the time scales of periodicities found in this case study.…”
Section: Discussion On the Precipitation-wind Relationship Over Sumamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Takayabu et al (1996) found out a quasi-2 day mode from cloud activities by GMS, rainfall data by meteorological radars, rawinsondes, a UHF wind profiler and meteorological buoy data over the equatorial Pacific, and identified it with westward propagating inertio-gravity waves. Widiyatmi et al (1999) found out a quasi-4 day mode in the Serpong BLR data, and GMS data in rainy seasons of Java Island, and considered that it may be mixed Rossby-gravity waves propagating westward. However, these are shorter than the time scales of periodicities found in this case study.…”
Section: Discussion On the Precipitation-wind Relationship Over Sumamentioning
confidence: 99%
“…A similar type of BLR has been operated at Serpong near Jakarta, West Java of Indonesia (6.4 S, 106.7 E) ( Fig. 1) since November 1992, and several studies related to cloud convection systems have been carried out (Hashiguchi et al 1995(Hashiguchi et al , 1996Widiyatmi et al 1999). At Kototabang, the first intensive observation had been conducted with BLR, GPS rawinsondes, ozonesondes and a tipping-buckettype rain gauge during 27 September-7 October 1998 in collaboration with Kobe University, Kyoto University and the University of Tokyo, Japan and BPPT (Agency for Assessment and Application of Technology) and BMG (Indonesian Meteorological and Geophysical Agency), Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Data on February 29 of a leap year have been omitted. By this pentad-mean procedure some equatorial wave-like components such as two-or four-day period modes (cf., Takayabu and Nitta 1993;Sato et al 1994;Widiyatmi et al 1999Widiyatmi et al , 2001) may be almost filtered out. Furthermore, the intraseasonal variations with 30-to 60-day periods have been removed from the pentad mean Table 2 and also indicated in Fig.…”
Section: Data and Analysis Methodsmentioning
confidence: 99%
“…In global climate studies by zonal-mean description, Oort and Yienger (1996) have discussed seasonal intensity of Hadley circulation on the basis of operational rawinsonde data, except for data around the Indonesian maritime continent. For vertical distributions of wind variations over Indonesia, a wind profiler station has been constructed near Jakarta (see Subsection 2.3), and several case studies have been done: a convection center passage at the beginning of rainy season (Hashiguchi et al 1995b), a mixed Rossby-gravity wave activity in the rainy season (Widiyatmi et al 1999(Widiyatmi et al , 2001, and others. Much longer-period data analysis has also been done (H. Hashiguchi, private communication), and striking year-to-year variations have been found, although these results have not been published.…”
Section: Introductionmentioning
confidence: 99%
“…These may be mixed Rossby-gravity waves [Yanai and Maruyama, 1966;Wheeler and Kiladis, 1999;Widiyatmi et al, 1999Widiyatmi et al, , 2001.…”
Section: Atmospheric Observationsmentioning
confidence: 99%